PENGARUH KOMUNIKASI ORGANISASI DAN KEPUASAN KERJA GURU TERHADAP KINERJA GURU DI KELOMPOK KERJA MADRASAH IBTIDAIYAH NEGERI 7 KABUPATEN CIREBON - Chaliqotul Karima (LPPM Bunga Bangsa Cirebon, 2019)
Teacher has a strategic role in improving the quality of education. However, the teacher’s performance in implementing 2013 curriculum is empirically not optimal in general. This study aimed to describe: Organizational Communication Variabels, Job Satisfaction, and Teacher Performance; Correlation of Organizational Communication with Job Satisfaction; Effect of Organizational Communication on Teacher Performance. This study used a quantitative approach using survey method with associative research types. The data collection technique used a questionnaire with a Likert measurement scale. The data were analysed by Regression Test and followed by Path Analysis. The results showed that Organizational Communication was very good (80.42%), Teacher’s Job Satisfaction was very good (82.94%), and Teacher Performance was good (79.67%). There was a positive and significant correlation between Organizational Communication and Job Satisfaction (r = 0.480). There was a positive and significant effect of Organizational Communication on Teacher Performance (0.380) and from Job Satisfaction with Teacher Performance (0.363). Simultaneously, there was a positive effect (0.532) and significant from Organizational Communication and Job Satisfaction on Teacher Performance. It can be concluded, in order to improve teacher performance in implementing the 2013 Curriculum, good organizational communication and high levels of job satisfaction are needed.